Classroom Action Research: Improving Students' Poetry Writing Skills Using Approaches Contextual Teaching and Learning - Hani Binti Abu Hassan, Ummi; Hidayani, Nurul; Nurhayati, Nurhayati; Melindawati, Silfi; Dahliana, Dina (International Journal of Elementary School, 2024)
Students find it difficult to express their ideas and select the appropriate words when writing poetry. This issue is supported by many students feeling bored during poetry writing lessons.The aim of this research is to determine the improvement of poetry writing skills using the Contextual Teaching and Learning approach in elementary school. This research is a Classroom Action Research study. The research was conducted in a fifth-grade class at an elementary school. The subjects of this research were all fifth-grade students, 18 students, consisting of 8 male students and 10 female students. Data collection techniques included observation, documentation, and testing. The data analysis technique consisted of four steps: the planning stage, the implementation stage, the observation stage, and the reflection stage. The results of the research show an improvement in poetry writing skills using the Contextual Teaching and Learning approach, as indicated by an increase in the average score from 75.58 in Cycle I to 83.69 in Cycle II. The percentage of learning outcome completion increased from 11 students (61.11%) in Cycle I to 17 students (94.44%) in Cycle II, Meeting II. The findings of this research can serve as initial data for future researchers studying this issue in different contexts and settings.